Self-reliance as a Concept and a Spatial Practice for Urban Refugees: Reflections from Delhi, India. (11th November 2019) - Field, Jessica; Tiwari, Anubhav Dutt; Mookherjee, Yamini
Abstract: In India, urban refugees sit within a legal vacuum and often struggle to make ends meet in the socio-economic periphery. The United Nations High Commissioner for Refugees and its implementing partners have focused on supporting refugees to achieve a level of self-reliance, primarily through market-based livelihood interventions. However, refugee lives in India's cities continue to be characterized by economic insecurity, exploitation and marginalization. This article explores the limitations of a market-orientated approach to fostering refugee self-reliance in the context of Delhi and departs from the burgeoning literature on refugee self-reliance by examining it from a spatial perspective. Building on recent work in political geography, the article highlights historic and ongoing practices of spatial exclusion of refugees and other poor migrant groups in India's capital city, as well as a diverse range of (non-economic) social networks and activities that have emerged as safety nets. We argue that, in addition to livelihoods, humanitarian actors must also explore non-economic initiatives that might contribute to refugee self-reliance and, importantly, must pay more attention to how the urban environment both delimits and enables these activities.